PENCEMARAN UDARA DAN MANAJEMEN LALU LINTAS DI INDONESIA - Nanny Kusminingrum (Direktorat Bina Teknik Jalan dan Jembatan, 2007)
The problem of air pollution has become an accute problem for many areas of cities , mostly in big cities. Bad air quality of city would decrease live quality of its people, unrealized. People breath an air to live. Serious impact to people’s health could be caused by an air that polluted with dangerous and poisoned particles There are seven main pollutan in air pollution : particulate (dust particles), Sulphure Dioxide (SO2), Ozone Troposferik, Carbon Monoxide (CO), Nitrogen Dioxide (NO2), Hidro Carbon (HC) and Pb. The main source of these pollutants are become from car’s gas emition. The problem above is going to worst with traffic jam in big cities in Indonesia. This happen because the worst condition of gas emition is when car’s engine running, while the car stop. A number of gas emition when the car stop could reach twice of a number of gas emition when the car run normally. This paper is trying to explain alternat ives strategic management that could be used in decreasing a number of air pollution caused by car’s gas emition. It’s including reduce a number of traffic jam’s spots in big cities. One of the strategic management that needed is traffic management. Generally, the traffic management’s strategy in this paper have two groups, which are : • A strategy that influence traffic flow or a strategy of controlling a number of car in each area. • A strategy that influenced the change of people’s transportation moda. The traffic management strategy alternatives stated in this paper are not rigid or unattached one-another. Variation, adjustments, or even collaboration between these strategies is a must, according to the characteristical differences between cities in which they are applied. Keywords : Air pollution, Emission, Motor vehicles, Congestion, Traffic management.